Expressions of private and public interests in the online news media coverage of emigration issues in Lithuania - Plepytė - Davidavičienė, Giedrė; Grebliauskienė, Beata (Information & Media, 2018)
[only abstract and keywords in English; full article, abstract and keywords in Lithuanian]This paper aims to determine how online news media represent the public interest in the discussion of emigration issues in Lithuania and how the coverage of emigration issues is affected by the need of consistency and adjustment between private and public interests. This study follows the idea that the pursuit of private and public interests motivates a different approach to the audience, and this, in its turn, conditions the coverage of the social issues that are relevant to society. In response to public interest, miscellaneous information is provided with a diversity of opinions and some degree of analysis, which sheds light on the causes of the problem and the possible solutions instead of presenting a mere account of compiled facts. In the provided analysis of the matter, we see that the satisfied private interest compels a recourse from shallowness, the presentation of overrated negative aspects, emotionality, and the discordance between the body and headlines of news texts.
Keywords: news/mass media, public interest, private interest, emigration